2023
DOI: 10.1021/acs.energyfuels.3c01466
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Models of Deep Hydrotreating Reactions to Produce Ultralow Sulfur Diesel

Abstract: Due to the current worldwide environmental problems caused by high emissions of polluting gases such as CO, NO x , and SO x , resulting from the combustion of fossil fuels, many organizations and governments have established standards aimed at producing cleaner and more environmentally friendly fuels. These standards focus on eliminating hazardous substances, particularly the sulfur compounds in diesel, as they are among the most harmful organic compounds to both human health and the environment. Hydrotreating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
(282 reference statements)
0
1
0
Order By: Relevance
“…[15] In order to calculate n Ni H 2 ð Þ, when the minimum H 2 consumption was achieved, the reaction product for each type of nitrides and the number of moles of H 2 consumed per mole of nitridesshould be identified. Studies showed that a pre-hydrogenation step of the N-containing ring was generally required before the breakage of C-N. [16] As listed in Table 2, when the minimum H 2 consumption was achieved during diesel hydrotreating, 1 mol of indole generated ethylbenzene consuming 3 mol of H 2 , and 1 mol of carbazole generated cyclohexylbenzene consuming 5 mol of H 2 , and 1 mol of quinoline generated propylbenzene consuming 4 mol of H 2 , and 1 mol of benzoquinoline generated 2-propylnaphthalene consuming 4 mol of H 2. The scheme of the above reactions are shown in Figure 2.…”
Section: Hdnmentioning
confidence: 99%
“…[15] In order to calculate n Ni H 2 ð Þ, when the minimum H 2 consumption was achieved, the reaction product for each type of nitrides and the number of moles of H 2 consumed per mole of nitridesshould be identified. Studies showed that a pre-hydrogenation step of the N-containing ring was generally required before the breakage of C-N. [16] As listed in Table 2, when the minimum H 2 consumption was achieved during diesel hydrotreating, 1 mol of indole generated ethylbenzene consuming 3 mol of H 2 , and 1 mol of carbazole generated cyclohexylbenzene consuming 5 mol of H 2 , and 1 mol of quinoline generated propylbenzene consuming 4 mol of H 2 , and 1 mol of benzoquinoline generated 2-propylnaphthalene consuming 4 mol of H 2. The scheme of the above reactions are shown in Figure 2.…”
Section: Hdnmentioning
confidence: 99%
“…The study of the reaction kinetics of ultradeep hydrodesulfurization (UHDS) of diesel has always been a hot research topic. , The commonly used hydrotreating reactors include fixed-bed, moving-bed, and ebullating-bed reactors. Fixed-bed reactors are the most commonly used reactor systems in commercial hydrotreating operations.…”
Section: Introductionmentioning
confidence: 99%